Analisis Minat Peserta Didik di SD Negeri 179 Tambangan Untuk Belajar Aktif di Dalam Kelas - Anisah Lubis; Novebri Novebri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the interest of students at SD Negeri 179 Tambangan in being active in class. It also aims to analyze the factors that influence students' interest in using interactive and participatory learning methods. The method employed is a survey of 100 students from different classes. Data were collected using a questionnaire consisting of closed and open-ended questions regarding learning experiences, interest in classroom activities, and preferences for the applied learning methods. The analysis shows that the majority of students are very interested in active learning, with 75% of respondents stating that discussion activitiesandeducationalgamesenhancetheirmotivation.However,thereare also challenges, such as a lack of equipment and limited time to implement these programs. These results provide valuable insights for educators in makingpolicies to develop more effective learning strategies. An increase in student interest is expected to improve the quality of education at SD Negeri 179 Tambangan.